2000
DOI: 10.21236/ada376639
|View full text |Cite
|
Sign up to set email alerts
|

Track Recognition Using Two-Dimensional Symbols or Three-Dimensional Realistic Icons

Abstract: Conventional tactical displays use nonrealistic two-dimensional (2-D) symbols to depict military assets. Prototypes of three-dimensional (3-D) tactical displays are being developed that depict assets using miniature realistic icons, mostly of ships and planes. Our objective was to test the performance benefits of these icons.In four experiments, we presented participants 10 common military platforms displayed as 3-D icons, 2-D icons, or conventional 2-D symbols (Military Standard 2525). We found that:• Symbols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The 3D conditions reliably outperformed 2D, with the ability to move or rotate the graph proving a valuable feature in 3D. Finally, Smallman, St. John, Oonk and Cowen [13] showed that 2D symbolic representations of military targets allowed faster and more accurate identification than 3D icons.…”
Section: Comparing 2d and 3d Interfacesmentioning
confidence: 95%
“…The 3D conditions reliably outperformed 2D, with the ability to move or rotate the graph proving a valuable feature in 3D. Finally, Smallman, St. John, Oonk and Cowen [13] showed that 2D symbolic representations of military targets allowed faster and more accurate identification than 3D icons.…”
Section: Comparing 2d and 3d Interfacesmentioning
confidence: 95%
“…Finally, Smallman et al (2000) showed that 2D symbolic representations of military targets allowed faster and more accurate identification than 3D icons. Wickens et al (1997) provide a fitting summary for prior work on 2D versus 3D evaluations:…”
Section: Spatial Cognition and User Interface Performancementioning
confidence: 99%
“…Recently, we measured the situation awareness of what was depicted in 3-D displays and compared it to 2-D control displays . We also compared the identifiability of conventional 2-D track symbols with realistic 3-D icons (Smallman, St. John, Oonk, and Cowen, 2000). Here, we examine the user's ability to localize tracks in space with 3-D displays.…”
Section: Introductionmentioning
confidence: 99%